2016
DOI: 10.1007/s10854-016-4593-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyester resin molecular weight on the performance of low temperature curing silver pastes

Abstract: Four polyester resins with different molecular weights were used as the binder phase in silver pastes. The effects of the polyester resin molecular weight on the performance of low temperature curing silver pastes were investigated. With increasing molecular weight, the resistivity first decreased and then increased, and the sample that used a polyester resin with a weight-average molecular weight of approximately 150,000 had the lowest resistivity of 3.673 9 10 -7 X m. After folding and smoothing the sample 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The half-reaction of ascorbic acid is C 6 H 6 O 6 + 2H + +2e = C 6 H 8 O 6 . The reduction electrode potential of C 6 H 8 O 6 can be calculated by the following equation: E = E 0 − 0.059 pH [ 24 ]. Therefore, the reducing ability of ascorbic acid can be adjusted by changing the pH value, and the reducing ability of ascorbic acid increases with the increase of pH value.…”
Section: Resultsmentioning
confidence: 99%
“…The half-reaction of ascorbic acid is C 6 H 6 O 6 + 2H + +2e = C 6 H 8 O 6 . The reduction electrode potential of C 6 H 8 O 6 can be calculated by the following equation: E = E 0 − 0.059 pH [ 24 ]. Therefore, the reducing ability of ascorbic acid can be adjusted by changing the pH value, and the reducing ability of ascorbic acid increases with the increase of pH value.…”
Section: Resultsmentioning
confidence: 99%
“…In this way the number of conductive network is increasing, leading to the rising of electrical conductivity. Liu C [18] synthesized the Ag paste by using 2µm Ag micron-akes and 20 nm Ag NPs, which has good conductivity of 3.673×10 − 5 Ω•cm. Jung [19] found that the mixed silver paste composed of Ag NPs and micron silver sheets had good adhesion and exibility, when the content of silver ake is 50%, the performance of silver paste is the best.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of matrix resin has also been studied. Studies have found that usually the film-forming resin is polyurethane, which has better electrical properties than epoxy resin [25][26][27]. The curing process [28] has also been studied.…”
Section: Introductionmentioning
confidence: 99%